Use of defatted flaxseed meal reduces precancerous colon lesions in C57BL/6 mice - Gomides,Antônio Frederico de Freitas (2013)
PURPOSE: To investigate the hemopreventive effect of defatted flaxseed meal in C57BL/6 mice after induction of precancerous colon lesions with 1.2-dimethylhydrazine (DMH). METHODS: Thirty-six 12-week-old C57BL/6 mice were divided into three treatment groups(n=12 in each group): (1) diet with 10% defatted flaxseed meal; (2) diet with defatted flaxseed meal and precancerous colon lesions induced by DMH; and (3) precancerous colon lesions induced by DMH, without defatted flaxseed meal. The incidence of aberrant crypt foci (ACF), oxidative processes, expression of tumor suppressor proteins and cyclins, as well as the profile of short-chain fatty acids (SCFA) in animal feces were investigated in the presence and absence of DMH. RESULTS: The rats consuming defatted flaxseed meals showed lesions with lower multiplicity and a reduced incidence of lesions. No changes in the expression of tumor suppressor proteins and those involved in cell cycle control were detected. CONCLUSION: Defatted flaxseed meal protected the distal colon of mice from precancerous lesions.